2018
DOI: 10.1002/2017jd027278
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Dry Deposition of Ozone to Vegetation

Abstract: Atmospheric ozone loss through dry deposition to vegetation is a critically important process for both air quality and ecosystem health. The majority of atmospheric chemistry models calculate dry deposition using a resistance‐in‐series parameterization by Wesely (1989), which is dependent on many environmental variables and lookup table values. The uncertainties contained within this parameterization have not been fully explored, ultimately challenging our ability to understand global scale biosphere‐atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
92
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(111 citation statements)
references
References 68 publications
16
92
0
1
Order By: Relevance
“…In general, differences between site and model environmental variables (e.g., meteorology or soil moisture) and observational uncertainty confound model evaluation (Cooter & Schwede, ; Schwede et al, ; Silva & Heald, ; Tuovinen et al, ; Z. Wu et al, ). To reduce the impact of differences between site and model variables on model evaluation and thus separate input uncertainty from process and parameter uncertainty (e.g., Z. Wu et al, ), we recommend driving standalone schemes with observed variables representative of the flux‐tower footprint.…”
Section: Simulating Ozone Dry Deposition In Regional and Global Modelsmentioning
confidence: 99%
“…In general, differences between site and model environmental variables (e.g., meteorology or soil moisture) and observational uncertainty confound model evaluation (Cooter & Schwede, ; Schwede et al, ; Silva & Heald, ; Tuovinen et al, ; Z. Wu et al, ). To reduce the impact of differences between site and model variables on model evaluation and thus separate input uncertainty from process and parameter uncertainty (e.g., Z. Wu et al, ), we recommend driving standalone schemes with observed variables representative of the flux‐tower footprint.…”
Section: Simulating Ozone Dry Deposition In Regional and Global Modelsmentioning
confidence: 99%
“…Furthermore, the spatial and seasonal variability of stomatal deposition in LM4.0 is dynamic, depending not only on LAI but also on climate conditions via their effects on plant functioning. In contrast, V d,O3 from the Wesely scheme in GEOS‐Chem generally increases from spring to summer, simply scaling with the seasonal changes in LAI (Silva & Heald, ), not accounting for variations during the wet versus dry season that are inferred from observations (section ) and from LM4.0 simulations for Mediterranean Europe, the U.S. Pacific Northwest, Mexico, and South Asia (Figures , , and ). Silva and Heald () showed that the Wesely scheme in GEOS‐Chem generally reproduces the seasonal mean observed V d,O3 averaged across sites globally but has limited skill ( R 2 = 0.04) in simulating the site‐to‐site variations in observations, supporting that the Wesely scheme has a lack of sensitivity to local environmental variables.…”
Section: Influence Of Changes In Ozone Deposition On Surface Ozonementioning
confidence: 99%
“…With a resistance‐in‐series framework, the Wesely scheme is well suited for inclusions in global models and has success in some applications when evaluating observed and modeled monthly mean climatology of V d,O3 averaged globally across sites for a particular land cover type (Silva & Heald, ; Val Martin et al, ; Wesely & Hicks, ). However, the substantial interannual variability and site‐to‐site differences in V d,O3 derived from measurements are not simulated by CTMs with the Wesely scheme driven by observed meteorology (Clifton et al, ; Silva & Heald, ). The expression for stomatal resistance used in the Wesely scheme is dependent on only solar radiation, air temperature, and leaf area index (LAI; Wesely, ; Kavassalis & Murphy, ).…”
Section: Introductionmentioning
confidence: 99%
“…The DNN model applied to the Hyytiälä test data has predictive skill, with performance as good or better than many theoretical parameterizations (Silva & Heald, ; Wu et al, ). However, the overall generalization error (error on the test set) of the DNN model as it applies to all mixed forests similar to Hyytiälä is likely underestimated in this situation because all of the data are not i.i.d.…”
Section: Resultsmentioning
confidence: 99%
“…We explore all possible months as a start date, and range from 1 to 12 months of continuous data throughout the year, with the DNN retrained on each combination of months. Figure shows that after approximately 6 months of continuous data collection (~2,800 observations) a generalization loss of within 50% of the fully trained DNN is reached, a value that should outperform the Weseley parameterization as implemented in GEOS‐Chem (Silva & Heald, ). In this specific case, training on months containing data from summers is more effective at reducing the generalization loss than winter months.…”
Section: Resultsmentioning
confidence: 99%